Antifungal susceptibility testing of yeasts: evaluation of technical variables for test automation. - Odds, F C (1995)
The technical parameters for antifungal susceptibility testing with Candida species were reexamined to determine the optimal conditions for testing with semiautomated preparations of broth microdilution cultures, automated spectrophotometric readings of the cultures, and dose-response and endpoint determinations by means of a computer spreadsheet. Tests were based on proposed standard method M27P of the National Committee for Clinical Laboratory Standards for antifungal agents. RPMI 1640 broth with extra glucose to a final concentration of 2% gave higher and more reproducible drug-free control readings without affecting susceptibility endpoint readings. An inoculum of 8 x 10(4) yeasts per ml prepared from a carbon-limiting broth culture without further standardization was found to give optimal control readings after 48 h of incubation at 37 degrees C. For flucytosine, fluconazole, itraconazole, and ketoconazole, endpoints based on 50% growth inhibition (50% inhibitory concentration) gave the minimum variation with inoculum size and the fewest endpoint differences with RPMI 1640 medium obtained from two different suppliers. The 50% inhibitory concentration was also the optimal endpoint for fluconazole and ketoconazole susceptibilities in comparison with broth macrodilution MICs determined by the method of the National Committee for Clinical Laboratory Standards. Intralaboratory reproducibility was determined by retrospective analysis of replicate results for isolates retested at random over a 2-year period. This approach showed less favorable reproducibility than has been reported from purpose-designed, prospective antifungal susceptibility studies, but it may better reflect real-life test reproducibility. Susceptibility data for 616 clinical isolates of yeasts, representing 16 Candida and Saccharomyces spp., confirmed the tendency of Candida lusitaniae isolates to show relatively low susceptibilities to amphotericin B, the tendency of Candida krusei isolates to show low flucytosine and fluconazole susceptibilities, and the presence of some isolates in the species Candida albicans, Candida glabrata, and Candida tropicalis with low susceptibilities to azole derivative antifungal agents. The study demonstrates the value of automation and standardization in all stages of yeast susceptibility testing, from plate preparation to data analysis.